A transdisciplinary approach to mentoring through collaboration. Issue 3 (1st December 2016) - Manjon, Sonia BasSheva; Ndzuta, Akhona; Greene, Chloé; Sarkar, Kaustavi (Cos); Flores, Nicholas (Nic); Guo, Wen
At The Ohio State University, I've had the honour and privilege to work with amazing students, both in the classroom and in community settings. We have engaged in collaborative research and service learning activities that created new knowledge and deep relationships. These relationships have supported a pedagogy of engagement that incorporates the tenants of collaboration and mentorship at multi-layered levels. They have also empowered both my students and community partners in the co-creation of knowledge that would lead to solutions of community-identified issues. The collaboration would be three tired and involve faculty, student and community, on equal platforms. The mentorship would navigate a process between my students and myself, equally playing significant roles in informing each other of new ideas and novel directions as we explored the issues, problems and concerns of our community partners. This article focuses on the co-creation of collaborative processes of faculty/student mentorship and collaboration between faculty/students, and faculty/students/community partners in the co-creation of knowledge.